The Impact of Product Design and Process Design towards New Product Performance in Manufacturing Industry: A Survey Result in Malaysia - Ahmad, Md Fauzi; Chun Hoong, Khor; Abdul Hamid, Norhadilah; Sarpin, Norliana; Zainal, Rozlin; Ahmad, Ahmad Nur Aizat; Hassan, Mohd Fahrul; Mohd Nawi, Mohd Nasrun (International Journal of Supply Chain Management, 2018)
New product design and process design are vital aspects for a company to survive in in global competition market. Product design determines in the success of a company through how product design can accomplish in todays marketplace and customer needs. Nevertheless, many new products which have been developed from research and development fail to compete in global market due to product performance issue such as quality, cost and delivery. Besides, many new product design is not capable to match with the process design and machine capability in production process. The objective of this paper is to identify the relationship between new product design and new product process design towards new product performance in manufacturing industry. Random sampling techniques have been used by distributing questionnaire to 400 companies in Malaysia manufacturing sector. 80 companies had replied with the respond rate of 20%. The result shows that the extent level of new product design and process design are moderate and high level respectively. Furthermore, there is a significant relationship between new product process design and new product performance (r(80) = 0.570, p < 0.05). However, there are no significant relationships between new product design and new product performance (r(80) = 0.092, p > 0.05). The study is important to gain insight on the effect of new product design and new product process design towards new product performance.